ZAP70 Related Severe Combined Immunodeficiency Initially Diagnosed as Incomplete (Atypical) Kawasaki Disease - Alexander, MD, Andrew; Pilichowska, MD, Monika (North American Journal of Medicine and Science, 2017)
ZAP70-related severe combined immunodeficiency (SCID) is a defect of the immune system characterized by absent or extremely low CD8+ T-cells and abnormal T-cell receptor signaling. This form of SCID is relatively rare with about 20 cases currently described in the literature and typically presents in infancy with recurrent opportunistic infections, failure to thrive, and gastrointestinal symptoms. This report describes a case of ZAP70-related SCID that was initially diagnosed as incomplete (atypical) Kawasaki disease. A 7-month-old infant presented with two weeks of fever, leukocytosis (33.5 K/μL) and anemia. No infectious etiology was identified and clinical presentation, along with laboratory work-up, suggested incomplete Kawasaki disease. He was treated with a single infusion of IVIG and 72 hours of high dose aspirin with resolution of fever. Seven months later, he presented again with three weeks of fever, persistent leukocytosis, failure to thrive and varicella infection following vaccination. During hospital admission, flow cytometric analysis was conducted to characterize atypical lymphocytes present in peripheral blood. The results revealed nearly absent CD8+ T-cells with a CD4+/CD8+ ratio of 40:1. Subsequent studies demonstrated the absence of ZAP70 expression on T-cells and NK-cells by flow cytometry. Additional testing revealed markedly decreased to absent CD45+ total lymphocyte proliferative response to mitogens and antigens. The patient was diagnosed with ZAP70-related SCID and was referred for further evaluation and bone marrow transplantation. He is currently doing well, apart from minor GVHD, 2 years post-transplant. [N A J Med Sci. 2017;10(1):29-31. DOI: 10.7156/najms.20171001029]